Changes in emergency department blood product use for major paediatric trauma following the implementation of a major haemorrhage protocol. (2nd April 2021) - Long, Elliot; Williams, Amanda; Babl, Franz E; Kinmonth, Anne; Tse, Wai Chung; Palmer, Cameron S; Crighton, Gemma; Savoia, Helen; Teague, Warwick J; Nystrup, Kristin Brønnum
Abstract: Objective: Fixed ratio blood product administration may improve outcomes in trauma patients with massive blood loss. The present study aimed to describe the impact of a major haemorrhage protocol (MHP) on the ratio of blood products administered for paediatric major trauma. Methods: Retrospective observational study in a state‐designated paediatric major trauma centre in Melbourne, Australia. Children with major trauma who received blood products in the ED were identified from a hospital trauma registry. Blood product ratios before, during and after implementation of a hospital MHP were compared in consecutive 2 year blocks. Results: Over a 6 year period, 767 major trauma patients were identified, of whom 47 received blood products in the ED and were included in the analysis; 14 pre‐MHP implementation, 24 during‐MHP implementation and nine post‐MHP implementation. No patients received blood products at a ratio of 1:1:1 for red blood cells:fresh frozen plasma:platelets, respectively, during any time period. In this cohort of predominantly blunt trauma, blood products were infrequently administered in the ED because of the low prevalence of massive blood loss. Coagulopathy and hypofibrinogenaemia were commonly observed, nearly half of included patients were managed operatively and one quarter did not survive their injuries. Conclusion: The implementation of a MHP did not change the ratio of blood product administration in this cohort of patients because of the infrequency of massive blood loss. Future studies may focus on the impact of treating coagulopathy and hypofibrinogenaemia on patient‐centred outcomes. Abstract : Blood products are used infrequently in paediatric major trauma due to the infrequency of massive blood loss. Major haemorrhage protocols do not change the ratio of blood products administered, and a shift in focus to address coagulopathy and hypofibrinogenaemia may be warranted.